A1.11 T cells in the infrapatellar fat pad of osteoarthritis patients as a source of IL-6 in the joint. (13th February 2015) - de Jong, AJ; Kwekkeboom, JC; Andersen, SN; Kloppenburg, M; Toes, REM; Ioan-Facsinay, A
Abstract : Background and objectives: The infrapatellar fat pad (IFP) is an adipose tissue organ present in the knee next to the synovium and cartilage, thereby constituting a potential player in the pathological processes in the osteoarthritic joint. Obesity-associated changes occur in IFP and this supports the hypothesis that IFP could mediate the association between obesity and the development and progression of osteoarthritis (OA). Interestingly, these changes were observed in the stromal vascular fraction (SVF) rather than adipocytes. As this fraction contain many different types of immune cells, we characterised the SVF of the IFP in OA patients phenotypically and functionally. Materials and methods: IFP samples were obtained from knee OA patients (N = 43) undergoing joint replacement surgery (58.1% women; mean (SD) age 66.4 years (10.9); mean (SD) BMI 29.2 kg/m 2 (5.7)). The SVF was isolated and cells were characterised based on surface markers expression and cytokine production using flow cytometry. Results: Characterisation of the SVF of IFP showed the presence of various immune cells in this tissue, whereby macrophages and T cells were most abundant. Interestingly, flow cytometry analyses of ex vivo cytokine production by different cells revealed a subpopulation of CD4 + T cells that were able to produce IL-6 without further stimulation. These IL-6 producing CD4 + T cells expressed CD69, indicating recent activation. Upon polyclonal stimulation, CD4 + T cells were able to secrete IFNγ, TNFα, and IL-4. However, IL-6 producing CD4 + T cells did not secrete these cytokines. Furthermore, chemokine receptor expression revealed that these IL-6 producing T cells could not be categorised as conventional T helper 1 (Th1), Th2, Th17 or Tfh cells. These data indicate that IL-6-secreting T cells are a distinct population of T cells. Finally, we have also studied whether these IL-6 producing T cells are also present in other tissues. Indeed, we have found these cells also in sc adipose tissues and synovium of OA patients, but only at low frequencies in blood. Conclusion: In conclusion, we have found a novel population of CD4 + T cells which secrete IL-6 directly ex vivo and are in an activated state, indicating that these CD4 + T cells might recognise adipose tissue antigens and could be involved in the inflammatory processes present in human adipose tissue. Moreover, they are a source of IL-6 in the OA joint, thereby potentially contributing to joint inflammation.